Practical API Design: Confessions of a Java Framework Architect - Tulach, Jaroslav (Apress, 2012)
“There are more than enough design books in the programming world already,” you might think. In fact, there are so many that it makes sense to ask why I would write—and especially why you would read—yet another one. Particularly, there is the famous Design Patterns: Elements of Reusable Object-Oriented Software,1 about design patterns in object-oriented systems, written by the so-called “Gang of Four,” which is a must read for every developer making use of any object-oriented language. In addition, there are many specialized books describing design patterns, all of them useful when writing specific types of applications. Moreover, there is the unofficial Java programmer’s bible, Effective Java.2 In light of these facts, is there really a need for yet another design book?